EFFICACY ASSESSMENT OF PATIENT-CONTROLLED EPIDURAL ANALGESIA IN OPERATIVE GYNECOLOGY FOR PATIENTS WITH HEART FAILURE - Valiev Sh. M.; Gaziyev Z. T. (Modern American Journals, 2025)
Background: Postoperative pain management in patients with pre-existing heart failure (HF) undergoing major gynecologic surgery presents a significant clinical challenge. Inadequate analgesia can precipitate myocardial ischemia and worsen HF symptoms by increasing sympathetic tone, oxygen consumption, and cardiac workload. Patient-Controlled Epidural Analgesia (PCEA) is a highly effective modality for postoperative pain relief following major abdominal and pelvic surgery, but its application in HF patients requires careful consideration of its hemodynamic effects. Objective: This article reviews the evidence and discusses the efficacy, safety, and role of PCEA as a strategy for enhanced recovery after surgery (ERAS) in operative gynecology patients with concomitant heart failure, guided by international anesthetic and cardiology society guidelines.
Keywords: Patient-Controlled Epidural Analgesia (PCEA), Operative Gynecology, Heart Failure (HF), Postoperative Pain Management, Enhanced Recovery After Surgery (ERAS), Hemodynamics.